Electrophysiological versus anatomical identification of midline myelotomy in intramedullary spinal cord tumors - Ahmed Hamdy Ashry; Mohamed Gabr; Mohammed F. A. Ali (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background In this retrospective study, we evaluated the utility of neurophysiological cord mapping in accurate identification of the midline for safe resection of intramedullary spinal cord tumors. We also determined the correlation between the anatomical and physiological midline. Eighteen patients with intramedullary spinal cord tumors underwent surgical resection at 2021–2024. We attempted to identify the midline for myelotomy using anatomical landmarks. We used phase reversal technique for dorsal cord mapping to confirm or correct the midline. Patients’ demographics, surgical details and clinical outcomes were recorded. The relation between the anatomical and physiological midline was analyzed statistically. Results Anatomical identification of the midline failed in 6 cases necessitating neurophysiological mapping. Correction of the anatomical midline by mapping was done in 3 patients. Postoperative assessment 3 months after surgery showed improvement in 6 of 9 patients with preoperative somatosensory deficits, with no new worsening neurological functions observed. Conclusion Intraoperative neurophysiological mapping using phase reversal technique is an essential tool to accurately locate the midline during resections of intramedullary spinal cord tumors particularly in cases with ambiguous anatomical landmarks.